Francesco Jovine's Le terre del Sacramento and the Occupation of the Land - Moloney, Brian (Spunti e Ricerche, 2016)
Luca Marano has long been represented as a Gramscian 'organic intellectual', but the question of how Jovine could convincingly represent a phenomenon that Gramsci said could not exist remains to be seen.